2022
DOI: 10.1002/jssc.202200305
|View full text |Cite
|
Sign up to set email alerts
|

Creatine@SiO2@Fe3O4 nanocomposite as an efficient sorbent for magnetic solid‐phase extraction of escitalopram and chlordiazepoxide from urine samples through quantitation via HPLC–UV

Abstract: rent study to prepare magnetic nanoparticles covered by cheap and nitrogen-rich creatine. The hydrothermal method was used for the synthesis of the magnetic core. The prepared magnetic core was then covered by SiO 2 and subsequently functionalized using creatine. The prepared creatine@SiO 2 @Fe 3 O 4 was utilized as a sorbent in the magnetic solid-phase extraction of the selected antidepressants including escitalopram and chlordiazepoxide as the model drugs. The extracted drugs were desorbed by a suitable orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…The developed method has low LODs and wide linear ranges. The overall results confirmed that our proposed method is simple, easy, relatively fast, repeatable, and sensitive [16, 1826].…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The developed method has low LODs and wide linear ranges. The overall results confirmed that our proposed method is simple, easy, relatively fast, repeatable, and sensitive [16, 1826].…”
Section: Resultssupporting
confidence: 71%
“…The overall results confirmed that our proposed method is simple, easy, relatively fast, repeatable, and sensitive [16,[18][19][20][21][22][23][24][25][26].…”
Section: Methods Evaluationsupporting
confidence: 75%
See 1 more Smart Citation
“…These MNCs exhibit distinct physical and chemical properties arising from the synergistic interactions between the different constituent metals 11,12 . Furthermore, an additional beneficial characteristic is the ability of the nanocatalyst to be easily recovered through the utilization of an external magnet, owing to its magnetic properties 13,14 . This approach effectively decreases the operational expenses and potentially facilitates the convenient reutilization of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…14 With MSPE, the target analytes are conveniently separated by the assistance of a magnetic eld, without the need for additional centrifugation or ltration steps, simplifying the pretreatment process and improving the extraction efficiency. 15 MSPE is frequently used for the extraction of pollutants from wastewater, chemicals derived from synthetic organic pollutants, pesticides, therapeutic medications, and heavy metal ions [16][17][18][19][20] due to its convenience, quick extraction process, good reusability, and environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%